Curvature effect on the mechanical behaviour of a martensitic shape-memory-alloy wire for applications in civil engineering. (14th January 2015) - Tran, Hanh; Balandraud, Xavier; Destrebecq, Jean-François
Abstract: The mechanical response of a bent shape memory alloy (SMA) wire is a key point for the understanding of the process of the creation of confining effects in a wrapped concrete cylinder for example. The objective of the present study is to model the phenomena involved in the bending of a martensitic SMA wire. The mechanism of martensite reorientation is considered in the model, which also takes into account the asymmetry between tension and compression. For validation purposes, experiments were performed on Ni–Ti wires: measurement of residual curvatures after bending release and tensile tests on pre-bent wires. In particular, the analysis shows a variation in axial stiffness as a function of the preliminary curvature. This result shows the necessity of modelling the distributions of the state variables within the wire cross-section for the simulation of confinement processes using SMA wires. It also opens prospects to potential application to the bending of SMA fibres in smart textiles.